A lithium metal negative electrode integrated material, a preparation method therefor, and an application thereof

CN122950443APending Publication Date: 2026-10-20JIANGSU ENPACK COMPOSITE CURRENT COLLECTORS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611157913.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-31
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

然而,现有研究多集中于在金属集流体(如铜箔)上蒸镀锂、蒸镀完成后再进行界面修饰、或基于电沉积体系研究锂成核行为,对于锂在电子绝缘固态电解质(如石榴石型LLZO)表面的蒸镀行为及界面同步调控机制研究较少

Benefits of technology

本发明将界面调控过程前移并嵌入锂金属蒸镀阶段,在蒸镀过程中同步完成锂沉积与界面构筑,使界面层在锂沉积初期即原位生成并与锂紧密结合,避免了后处理界面易脱落或接触不良的问题,有效提升了界面的一致性与稳定性,简化了工艺路线。本发明中,COF多孔骨架提供的均匀成核位点与单原子金属对电子分布和局域电场的调控协同作用,使锂在电子绝缘的固态电解质表面实现均匀成核与连续致密沉积,克服了绝缘基底上蒸镀锂易形成岛状结构的技术难题。另外,原位同步构筑的稳定界面减少了界面空隙与不良结合,提高了离子传输效率,从而显著降低电化学界面阻抗并改善电池的循环性能;在后续电化学循环中,该复合界面层还能缓解锂金属与固态电解质之间的接触劣化并抑制锂体积膨胀。本发明将蒸镀锂的应用场景由导电集流体拓展至电子绝缘固态电解质表面,实现了电极与电解质界面的直接耦合,为高性能一体化固态锂金属电池的构筑与产业化提供可行的技术路径。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_5
    Figure SMS_5
Patent Text Reader

Abstract

This invention provides an integrated lithium metal anode material, its preparation method, and its application, belonging to the field of solid-state battery technology. Addressing the problems of uneven lithium deposition, poor interfacial contact, and high impedance on the surface of the electronically insulating solid electrolyte in solid-state batteries, this invention grows a covalent organic framework (COF) layer in situ on the solid electrolyte surface and loads a single-atom metal to form a composite interface layer. Subsequently, lithium metal is vacuum-deposited onto this interface. Utilizing the synergistic effect of the physical confinement of the porous COF structure and the chemical regulation of the single-atom metal, uniform nucleation and dense growth of lithium atoms are guided, achieving simultaneous integration of lithium deposition and interface construction. This invention breaks through the traditional step-by-step process of "preparing the lithium anode first, then modifying the interface," solves the problem of "island-like" growth of lithium deposition on the insulating substrate, effectively reduces interfacial impedance, and provides a new solution for constructing integrated high-performance solid-state lithium metal batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solid-state lithium metal battery technology, and more specifically, to an integrated lithium metal anode material, its preparation method, and its application. Background Technology

[0002] Lithium metal anodes possess extremely high theoretical specific capacity (3860 mAh / g) and extremely low electrochemical potential (-3.04 V vs. Li / Li). + Lithium metal is considered a key anode system for breaking through the bottleneck of next-generation high-energy-density batteries. In all-solid-state batteries, the combination of lithium metal and highly stable solid electrolyte is considered an important path to fundamentally solve the contradiction between safety and energy density. In recent years, integrated lithium metal batteries have attracted widespread attention. This type of system aims to build a continuous structure without obvious interface separation inside the battery to minimize interface impedance and improve structural stability. The quality of lithium metal construction on the surface of the solid electrolyte directly determines the interface performance.

[0003] Traditional lithium metal anodes primarily rely on rolled lithium foil or pressed lithium sheets. During solid-state battery assembly, these lithium metals often suffer from poor contact, interfacial voids, and localized stress concentrations with the solid electrolyte, leading to increased interfacial impedance, lithium dendrite growth, and even interfacial failure. With the development of physical vapor deposition (PVD) technology, evaporated lithium has gradually been used to prepare ultrathin lithium anodes. Its nanoscale thickness control and highly uniform deposition characteristics allow for the direct construction of lithium metal layers on the surface of the solid electrolyte, extending beyond the current collector surface and providing a new pathway for integrated battery structures. However, current research largely focuses on evaporating lithium onto metal current collectors (such as copper foil), followed by interface modification, or studying lithium nucleation behavior based on electrodeposition systems. There is limited research on the evaporation behavior of lithium on electronically insulating solid electrolytes (such as garnet-type LLZO) and the synchronous interfacial regulation mechanisms.

[0004] Most existing interface modification methods are performed after lithium metal preparation, such as coating an artificial solid electrolyte interphase (SEI) layer on the lithium layer surface. This post-processing approach cannot simultaneously control the interface structure during lithium formation, and the bond between the post-constructed interface layer and the lithium metal is weak, making it prone to detachment or poor contact during cycling. Meanwhile, when lithium is vapor-deposited on an electronically insulating substrate, the lack of continuous electron transport paths and effective nucleation sites causes lithium atoms to grow in an island-like pattern, making it difficult to form a continuous and dense metal layer. This further limits the application of vapor-deposited lithium in integrated solid-state batteries.

[0005] In view of this, the present invention is proposed. Summary of the Invention

[0006] The purpose of this invention is to provide an integrated lithium metal anode material, its preparation method, and its application.

[0007] This invention is implemented as follows: In a first aspect, the present invention provides an integrated lithium metal anode material, comprising a modified solid electrolyte and a lithium metal layer physically deposited on the surface of the modified solid electrolyte, wherein the modified solid electrolyte comprises a solid electrolyte substrate and a composite interface layer covering the surface of the solid electrolyte substrate; the composite interface layer comprises a solid electrolyte, a covalent organic framework layer (COF), and a single-atom metal modified in the covalent organic framework layer (COF).

[0008] In an optional embodiment, the single-atom metal in the composite interface layer is at least one of cobalt, iron, or nickel.

[0009] In an optional embodiment, the covalent organic framework layer (COF) in the composite interface layer contains cyano groups.

[0010] In an optional embodiment, the solid electrolyte includes an oxide solid electrolyte with hydroxyl groups on its surface and a sulfide solid electrolyte.

[0011] In an optional embodiment, the oxide solid electrolyte includes at least one of LLZO and LLTO; the sulfide solid electrolyte includes at least one of silver sulfide germanite type LPSCl, LPSBr, LPSI and LGPS type.

[0012] Secondly, the present invention provides a method for preparing the lithium metal anode integrated material as described above, comprising the following steps: S1, In-situ growth of a covalent organic framework layer (COF) on the surface of a solid electrolyte material; S2, Loading a single-atom metal onto the covalent organic framework layer COF to obtain a composite interface material; S3, the composite interface material is dispersed in a solvent to prepare a composite interface slurry; S4, the solid electrolyte substrate is coated with the composite interface slurry to obtain the modified solid electrolyte; S5, lithium metal is vapor-deposited on the modified solid electrolyte, so that gaseous lithium atoms grow along the composite interface layer on the surface of the modified solid electrolyte to form a lithium metal layer, thereby obtaining an integrated lithium metal anode material.

[0013] In an optional implementation, in S2, a single-atom metal is loaded onto a covalent organic framework layer (COF) by ultrasonic impregnation.

[0014] In an optional embodiment, the thickness of the covalent organic framework layer is 5~15 nm.

[0015] In an optional embodiment, the thickness of the lithium metal layer is 1~50 μm.

[0016] Thirdly, the present invention provides a solid-state lithium metal battery, comprising the above-mentioned lithium metal anode integrated material, or the lithium metal anode integrated material prepared by the above-mentioned preparation method.

[0017] The present invention has the following beneficial effects: This invention moves the interface regulation process forward and embeds it into the lithium metal evaporation stage, simultaneously completing lithium deposition and interface construction during the evaporation process. This allows the interface layer to form in situ and tightly bond with lithium in the early stages of lithium deposition, avoiding the problems of easy interface detachment or poor contact in post-processing. This effectively improves the consistency and stability of the interface and simplifies the process route. In this invention, the uniform nucleation sites provided by the COF porous framework and the synergistic effect of the single-atom metal's regulation of electron distribution and local electric field enable uniform nucleation and continuous dense deposition of lithium on the surface of an electronically insulating solid electrolyte, overcoming the technical challenge of forming island-like structures when evaporating lithium on an insulating substrate. In addition, the stable interface constructed in situ simultaneously reduces interfacial voids and poor bonding, improving ion transport efficiency, thereby significantly reducing electrochemical interface impedance and improving battery cycle performance. In subsequent electrochemical cycles, this composite interface layer can also alleviate contact degradation between lithium metal and the solid electrolyte and suppress lithium volume expansion. This invention expands the application of evaporated lithium from conductive current collectors to the surface of electronically insulating solid electrolytes, realizing direct coupling between the electrode and electrolyte interface, and providing a feasible technical path for the construction and industrialization of high-performance integrated solid-state lithium metal batteries. Detailed Implementation

[0018] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0019] In a first aspect, the present invention provides an integrated lithium metal anode material, comprising a modified solid electrolyte and a lithium metal layer physically deposited on the surface of the modified solid electrolyte, wherein the modified solid electrolyte comprises a solid electrolyte substrate and a composite interface layer covering the surface of the solid electrolyte substrate. The composite interface layer includes a solid electrolyte, a covalent organic framework layer (COF), and a single-atom metal modified in the COF.

[0020] This invention provides an integrated lithium metal anode material, obtained by vacuum evaporation deposition of a lithium metal layer on the surface of a modified solid electrolyte. First, a covalent organic framework (COF) layer is grown in situ on the solid electrolyte surface, and single-atom metal is coordinated within the COF layer to form a composite interface layer with both porous structure and single-atom active sites. This composite interface layer is then coated onto a solid electrolyte substrate. The porous framework of the COF layer provides a high specific surface area and uniformly distributed lithium nucleation sites, reducing local nucleation overpotential. The single-atom metal is anchored in the COF channels through MN coordination bonds, resulting in a much higher atomic utilization rate than nanoparticles or clusters. This allows for the regulation of electron distribution and local electric field at the interface, enhancing the adsorption capacity of lithium atoms at the interface. The resulting modified solid electrolyte surface exhibits excellent lithiophilicity and nucleation control capabilities.

[0021] After obtaining the modified solid electrolyte, this invention achieves simultaneous integration of lithium deposition and interface construction by vacuum evaporation deposition of a lithium metal layer on the surface of the modified solid electrolyte. During the evaporation process, gaseous lithium atoms preferentially adsorb and nucleate in the porous structure of the COF layer. The regular one-dimensional channels of the COF guide the directional migration of lithium atoms along the channels to achieve continuous and dense epitaxial growth. Simultaneously, single-atom Co participates in the interfacial reaction in the early stage of lithium deposition to form a Co-Li alloy, reducing the nucleation barrier and suppressing random nucleation behavior. The resulting integrated material has a continuous, dense, non-island structure of lithium metal layer, which is tightly coupled with the COF-Co interface layer, exhibiting low interfacial impedance and strong bonding force, fundamentally solving the problems of uneven lithium deposition and poor interfacial contact on electronically insulating substrates.

[0022] In an optional embodiment, the solid electrolyte substrate and the solid electrolyte in the composite interface layer may be made of the same or different materials.

[0023] In an optional embodiment, the solid electrolyte in the composite interface layer includes an oxide solid electrolyte and a sulfide solid electrolyte with hydroxyl groups on the surface.

[0024] In an optional embodiment, the hydroxyl group is derived from intrinsic -OH groups on the surface of the solid electrolyte or -OH groups generated on the surface of the solid electrolyte after pretreatment.

[0025] The hydroxyl groups (-OH) on the surface of the solid electrolyte (such as LLZO) in the composite interface layer have lone pairs of electrons, which can form Schiff base condensation reactions with the aldehyde groups (-CHO) of the COF monomer. This allows the COF layer to be directly anchored to the solid electrolyte surface via covalent bonds, rather than through simple physical adsorption or mixing. This chemical bonding method endows the interface layer with excellent binding force and stability.

[0026] In an optional embodiment, the average particle size of the solid electrolyte material is preferably 200-500 nm, more preferably 400 nm.

[0027] The coordination environment of atomic metals in the COF layer involves the synergistic effect of MN coordination bonds and cyano groups (-CN). Nitrogen atoms in the COF framework act as coordination sites, forming stable MN coordination bonds with metal ions. Simultaneously, the cyano group, as an electron-withdrawing group, can further modulate the electron density of the metal sites. This coordination environment results in highly dispersed metal single atoms in the COF layer, with an atomic utilization rate approaching 100%, far exceeding that of nanoparticles or clusters. Single-atom metals can modulate the electron distribution and local electric field at the interface, enhancing the adsorption and stabilization ability of lithium atoms at the interface, reducing the nucleation overpotential of lithium atoms, and guiding lithium atoms to achieve preferential rather than random nucleation. In subsequent electrochemical cycling, the electronic regulation effect of metal single atoms helps to homogenize the lithium-ion flux and suppress dendrite growth.

[0028] In an optional embodiment, the monatomic metal is selected from transition metals.

[0029] The d-orbital electronic structure of transition metal atoms enables them to form stable MN coordination bonds with nitrogen atoms in the COF framework. This allows them to be highly dispersed and anchored in the COF channels as single atoms, and their unfilled d-orbitals regulate the electron distribution and local electric field at the interface, thereby reducing the nucleation overpotential of lithium atoms. Any transition metal capable of forming MN coordination bonds with nitrogen atoms in the COF framework and having a regulatory effect on lithium nucleation behavior can be used in this invention.

[0030] In an optional embodiment, the single-atom metal is preferably at least one of cobalt, iron, and nickel.

[0031] More preferably, the single-atom metal is cobalt, which can form a Co-Li alloy with lithium in the early stage of lithium deposition, thus having the most significant effect on reducing the nucleation barrier.

[0032] In an optional embodiment, the solid electrolyte substrate is an electronically insulating solid electrolyte substrate.

[0033] In optional embodiments, the solid electrolyte substrate is preferably a garnet-type solid electrolyte, more preferably Li7La3Zr2O. 12 (LLZO).

[0034] In an optional embodiment, the covalent organic framework layer (COF) in the composite interface layer contains cyano groups.

[0035] The cyano group (-CN) is a strong electron-withdrawing group, which gives the COF framework a lithium-loving property. The nitrogen atom in the cyano group can form a Li-N coordination with the lithium atom, which lowers the diffusion barrier of lithium atoms in the COF channels, allowing lithium atoms to migrate directionally along the regular one-dimensional channels of the COF, thereby achieving continuous and dense epitaxial growth.

[0036] In an optional embodiment, the thickness of the covalent organic framework layer (COF) is 5-15 nm.

[0037] The thickness of the COF layer directly affects the ion transport performance and structural stability of the interface layer. An excessively thin COF layer cannot provide enough single-atom loading sites and lithium nucleation sites; an excessively thick COF layer increases the ion transport path length and interface impedance. A thickness range of 5-15 nm strikes a balance between the functionality of the interface layer and ion transport efficiency.

[0038] In an optional embodiment, the thickness of the lithium metal layer is 1-50 μm, preferably 5-20 μm.

[0039] In an optional embodiment, the lithium metal layer is deposited on the surface of the modified solid electrolyte by a vacuum evaporation process to form a multilayer structure of Li metal layer / COF-Co@LLZO interface / LLZO.

[0040] In an optional implementation, the thickness of the composite interface layer is 50~100 μm.

[0041] Secondly, the present invention provides a method for preparing the lithium metal anode integrated material as described above, comprising the following steps: S1, In-situ growth of a covalent organic framework layer (COF) on the surface of a solid electrolyte material; S2, Loading a single-atom metal onto the covalent organic framework layer COF to obtain a composite interface material; S3, the composite interface material is dispersed in a solvent to prepare a composite interface slurry; S4, the solid electrolyte substrate is coated with the composite interface slurry to obtain the modified solid electrolyte; S5, lithium metal is vapor-deposited on the modified solid electrolyte, so that gaseous lithium atoms grow along the composite interface layer on the surface of the modified solid electrolyte to form a lithium metal layer, thereby obtaining an integrated lithium metal anode material.

[0042] The preparation method provided in this paper includes five steps: in-situ growth of a COF layer on a solid electrolyte surface, loading of a single-atom metal, coating, and evaporation of lithium metal. It utilizes the Schiff base condensation reaction between hydroxyl groups on the solid electrolyte surface and aldehyde groups of the COF monomer to achieve in-situ chemical bonding growth of the COF layer. The single-atom metal is anchored in the COF channels via ultrasonic impregnation in an MN coordination manner. During the evaporation process, the physical confinement effect of the porous COF framework and the chemical regulation effect of the single-atom metal synergistically guide the uniform nucleation and directional growth of lithium atoms, achieving integrated construction of lithium generation and interface building simultaneously. The resulting Li metal layer / COF-Co@LLZO interface / LLZO multilayer structure exhibits significantly better interface consistency and stability than the traditional stepwise process of "preparing lithium metal first and then modifying the interface," while also simplifying the process flow and making it suitable for large-scale production.

[0043] In an optional embodiment, in S1, the solid electrolyte is pretreated.

[0044] In an optional implementation, the preprocessing includes: The solid electrolyte is placed in a Piranha solution and treated at 50-70°C for 0.5-2 hours. The Piranha solution is prepared by mixing concentrated H2SO4 and 30% H2O2 in a volume ratio of 2:1-4:1. After treatment, the electrolyte is washed sequentially with deionized water until neutral, then with ethanol, and dried in a vacuum oven at 60-100°C for 6-24 hours.

[0045] In an optional embodiment, the volume ratio of concentrated H2SO4 to 30% H2O2 in the Piranha solution is 3:1.

[0046] Piranha solution possesses strong oxidizing properties, introducing abundant -OH groups onto the surface of the solid electrolyte. These hydroxyl groups serve as anchoring sites for the in-situ growth of the COF layer, forming covalent bonds with the COF monomers through Schiff base condensation reactions. This ensures the strength of the chemical bond between the COF layer and the substrate, preventing interfacial separation under the high-temperature, high-vacuum conditions of subsequent vapor deposition processes. The pretreated solid electrolyte surface exhibits a significantly increased hydroxyl density, which substantially enhances the uniformity of the COF layer coating and the interfacial adhesion.

[0047] In an optional implementation, S1 specifically includes: The solid electrolyte substrate was ultrasonically dispersed in a mixed solvent, and COF monomers TFPpy and Bcbpy were added. The mixture was ultrasonicated for another 5-10 minutes. Then, a DBU catalyst solution (5M, 30-70 μL) was added, and the mixture was ultrasonicated for another 10 minutes. The reaction system was then placed in an 80°C oil bath and stirred for 24-48 hours. After the reaction was completed, the product was separated by centrifugation and washed three times each with tetrahydrofuran and methanol. The product was then vacuum dried overnight at 60°C to obtain COF@solid electrolyte.

[0048] In an optional embodiment, the mixed solvent is a mixture of 1,2-dichlorobenzene and 1-butanol, wherein the volume ratio of 1,2-dichlorobenzene to 1-butanol is 1:1.

[0049] In an optional embodiment, the amount of TFPpy is 1.85~7.4 mg / 100mg solid electrolyte, the amount of Bcbpy is 1.45~5.75 mg / 100mg solid electrolyte, and the molar ratio of TFPpy to Bcbpy is 1:1.

[0050] In-situ growth of the COF layer is based on the Schiff base condensation reaction mechanism. TFPpy contains aldehyde groups (-CHO), and Bcbpy contains amino groups (-NH2). Under the action of a DBU alkaline catalyst, they undergo a condensation reaction to form a Schiff base framework containing C=N bonds, thereby constructing an ordered covalent organic framework structure. Since step S1 introduces abundant -OH groups onto the solid electrolyte surface, these -OH groups can react similarly with the aldehyde groups of TFPpy, anchoring the COF layer to the solid electrolyte surface via covalent bonds, achieving true in-situ chemical bonding growth with a much stronger binding force than physical coating methods. By adjusting the monomer concentration and reaction time, the thickness of the COF layer can be precisely controlled within the range of 5-15 nm to meet the needs of different application scenarios.

[0051] In an optional embodiment, in S2, a single-atom metal is loaded onto the covalent organic framework layer by ultrasonic impregnation, specifically including: The COF@solid electrolyte obtained in step S1 was dispersed in methanol with a metal salt, sonicated at room temperature for 2-6 hours, then centrifuged and washed 2-4 times with methanol, and dried under vacuum at 60°C overnight to obtain COF-single-atom metal@solid electrolyte.

[0052] In an optional embodiment, the metal salt is a soluble salt of a transition metal, including at least one of chlorides, nitrates, and acetates of a transition metal; preferably, the metal salt is at least one of cobalt salts, iron salts, nickel salts, copper salts, manganese salts, and zinc salts, and more preferably CoCl2·6H2O.

[0053] In an optional embodiment, the amount of the metal salt is calculated as 5-15 wt% of the COF mass, preferably 10 wt%.

[0054] In an optional embodiment, the ultrasound duration is 2-6 hours, preferably 4 hours.

[0055] The principle of ultrasonic impregnation for loading single-atom metals is to utilize the cavitation effect of ultrasound to generate a localized high-temperature, high-pressure microenvironment, promoting the diffusion and penetration of metal ions into the pores of the COF (Co-ionized Air Foil). Nitrogen atoms in the COF framework (derived from cyano groups, pyridine nitrogen, etc.) act as coordination sites, interacting with metal ions (such as Co...). 2+ Stable MN coordination bonds are formed, anchoring the metal in single-atom form within the COF channels, creating highly dispersed single-atom metal active sites. Room-temperature ultrasonic treatment avoids the risk of COF layer structure destruction under high-temperature conditions. After single-atom metal loading, the original thickness of the COF layer remains unchanged (5-15 nm), without significant thickening due to metal loading. The high dispersion of single-atom Co in the COF layer allows for near 100% atomic utilization, far exceeding that of nanoparticles or clusters, thus achieving significant interface control effects with extremely low metal usage.

[0056] In an optional embodiment, the thickness of the covalent organic framework layer is 5~15 nm.

[0057] In an optional embodiment, step S3 includes: dispersing the COF-single-atom metal@solid electrolyte powder obtained in step S2 in an organic solvent, adding a dispersant, and ultrasonically treating the powder to make it uniformly suspended, thereby obtaining a slurry; In an optional embodiment, the organic solvent is N-methylpyrrolidone (NMP); the dispersion concentration of the COF-single-atom metal@solid electrolyte powder is 5-10 mg / mL; the dispersant is polyvinylpyrrolidone (PVP); the amount of the dispersant is 0.5-1 wt%; and the ultrasonic treatment time is 15-45 minutes.

[0058] In an optional embodiment, the coating method is blade coating, and the drying and curing process includes: first, allowing the solvent to evaporate naturally in air for 5-10 minutes, followed by drying under a vacuum atmosphere at 60-80°C for 6-24 hours, preferably 12 hours. The thickness of the composite interface layer after drying and curing is 50-100 μm.

[0059] The purpose of the coating process is to uniformly coat COF-Co@ solid electrolyte powder onto the surface of a solid electrolyte substrate, forming a composite interface layer with controllable thickness. NMP, as a solvent, has good solubility and volatility, while PVP, as a dispersant, prevents powder agglomeration and improves the uniformity and stability of the slurry. A two-step drying method—first evaporating in air and then vacuum drying—avoids the internal stress and cracking problems caused by rapid solvent evaporation. The coated composite interface layer is uniform and dense, adhering tightly to the solid electrolyte substrate, and will not peel off or delaminate during subsequent vapor deposition processes. The coating process is simple and controllable, suitable for large-scale production.

[0060] In an optional embodiment, step S5 includes: transferring the modified solid electrolyte obtained in step S4 to a vacuum evaporation coating system for lithium metal evaporation deposition.

[0061] In an optional embodiment, the vapor deposition method is thermal evaporation or electron beam evaporation, and the evaporation source is high-purity lithium metal particles or lithium blocks with a purity of not less than 99.9%.

[0062] In an optional embodiment, during the vapor deposition process, the deposition chamber is first evacuated to a high vacuum state, so that the substrate vacuum degree reaches ≤5×10⁻⁶. -5 Pa; then, lithium metal is evaporated and deposited on the substrate surface by heating the evaporation source, the evaporation temperature is controlled at 400-600℃, the evaporation rate is controlled at 1~10 nm / s, and the substrate temperature is maintained at room temperature 20-30℃; the thickness of the deposited lithium metal layer is 1-50 μm, preferably 5-20 μm, by adjusting the evaporation time.

[0063] During the evaporation of lithium metal, gaseous lithium atoms reach the substrate surface with a certain kinetic energy in a high vacuum. Due to the following characteristics of the COF-Co interface layer, the nucleation and growth behavior of lithium atoms are synergistically guided: (1) The porous structure of the COF layer provides a large number of uniformly distributed nucleation sites, reducing the local nucleation overpotential; (2) Single-atom Co and lithium atoms form a Co-Li alloy, further reducing the nucleation barrier; (3) The cyano group in the COF framework forms a Li-N coordination with lithium atoms, enhancing the adsorption stability of lithium atoms in the COF channels. Under the above triple effect, lithium atoms preferentially nucleate uniformly in the porous structure of the COF layer, and achieve directional migration and continuous dense epitaxial growth along the regular one-dimensional channels of COF, ultimately forming a continuous dense lithium metal layer tightly coupled with the COF-Co interface layer. The resulting lithium metal layer is continuous and dense, with a non-island structure, and is in close contact with the COF-Co interface layer, without voids or poor bonding, resulting in low interface impedance. The vapor deposition process parameters are precisely controllable, and can achieve precise control within the thickness range of 1-50μm. Most importantly, the interface is constructed synchronously during the vapor deposition process, avoiding the problem of delayed interface formation in traditional processes.

[0064] In an optional embodiment, the thickness of the lithium metal layer is 1~50 μm.

[0065] Thirdly, the present invention provides a solid-state lithium metal battery, comprising the above-mentioned lithium metal anode integrated material, or the lithium metal anode integrated material prepared by the above-mentioned preparation method.

[0066] In an optional embodiment, the cathode material of the solid-state lithium metal battery is NMC and / or LFP.

[0067] Solid-state lithium metal batteries assembled based on the lithium metal anode integrated material provided by this invention exhibit excellent cycle stability and rate performance due to their low interface impedance and uniform and dense lithium metal layer.

[0068] The features and performance of the present invention will be further described in detail below with reference to embodiments.

[0069] Example 1 This embodiment provides a method for preparing an integrated lithium metal anode material, and the resulting integrated lithium metal anode material and a solid-state lithium metal battery, specifically including the following steps: (1) Preparation of COF-Co@LLZO 1. LLZO surface pretreatment LLZO powder with an average particle size of 400 nm was placed in Piranha solution (concentrated H2SO4: 30% H2O2 = 3:1) and treated at 60 °C for 1 hour. It was then washed with a large amount of deionized water until neutral, then washed three times with ethanol, and finally dried in a vacuum oven at 80 °C for 12 hours to obtain LLZO powder with hydroxyl-rich surface.

[0070] 2. In-situ growth of COF on LLZO surface 100 mg of pretreated LLZO was ultrasonically dispersed in 0.5 mL of a mixed solvent (1,2-dichlorobenzene:1-butanol = 1:1 Vol.%), followed by the addition of 3.7 mg TFPpy and 2.9 mg Bcbpy, and sonication continued for 5 minutes. Then, 50 μL of DBU solution (5 M) was added, and the mixture was sonicated for 10 minutes. The reaction system was then placed in an 80 °C oil bath and stirred for 24 hours. After the reaction was complete, the mixture was centrifuged, washed three times each with tetrahydrofuran and methanol, and dried under vacuum at 60 °C overnight to obtain COF@LLZO. The coating thickness was approximately 10 nm.

[0071] 3. Coordination loading of Co single atoms 100 mg COF@LLZO and 10 mg CoCl2·6H2O were dispersed in 20 mL of methanol and sonicated at room temperature for 4 h. After centrifugation, the mixture was washed three times with methanol and dried under vacuum at 60°C overnight to obtain COF-Co@LLZO.

[0072] (2) Coating 1. Solution dispersion COF-Co@LLZO powder was dispersed in NMP at a concentration of 8 mg / mL, and 0.5 wt% PVP was added as a dispersant. The mixture was ultrasonically treated for 30 minutes to obtain a uniform suspension slurry.

[0073] 2. Scalpel coating The above slurry was poured onto an LLZO ceramic substrate and coated with a scraper to form a wet film on the substrate. After drying, the dry film thickness was 75 μm.

[0074] 3. Drying and curing After coating, allow the solvent to evaporate naturally in the air for 8 minutes, and then dry at 70 °C for 12 hours under vacuum to ensure that the COF-Co layer adheres tightly to the LLZO surface.

[0075] (3) Evaporation of lithium metal The coated sample was transferred to a vacuum evaporation coating system for lithium metal deposition. The evaporation source was high-purity lithium metal particles (99.9% purity), and the vacuum level in the deposition chamber was ≤5×10⁻⁶. -5 Pa. Lithium metal was evaporated and deposited onto the substrate surface by heating the evaporation source. The evaporation temperature was controlled at 500℃, the deposition rate at 5 nm / s, and the substrate temperature was maintained at 25℃. The deposition time was adjusted to achieve a lithium metal layer thickness of 10 μm.

[0076] During the lithium deposition process, lithium first deposits in the porous structure of the COF layer and uniformly nucleates to form a continuous and dense lithium metal layer. At the same time, the Co element in the COF layer participates in the interfacial reaction in the early stage of lithium deposition to form an alloy and reduce the nucleation barrier. Finally, a Li metal layer / COF-Co@LLZO interface / LLZO multilayer structure is formed, constructing an integrated lithium metal anode and solid electrolyte structure.

[0077] Battery assembly is performed in an inert atmosphere glove box, wherein the glove box environment is an argon protective atmosphere with H2O content less than 0.1 ppm and O2 content less than 0.1 ppm. The prepared integrated lithium metal anode / solid electrolyte is assembled with a cathode material (NMC or LFP) to form a solid-state lithium metal battery. The assembly method can be a laminated structure, a coin cell structure, or a pouch cell structure.

[0078] Example 2 The only difference between this embodiment and Example 1 is the adjustment of the monomer dosage and reaction time for in-situ COF growth, controlling the COF layer thickness to 5 nm. Specifically, the dosage of TFPpy was adjusted to 1.85 mg, the dosage of Bcbpy was adjusted to 1.45 mg, and the oil bath reaction time was shortened to 12 h. All other raw materials, steps, and parameters remained consistent with Example 1. A lithium metal anode integrated material with a lithium metal layer thickness of 10 μm was finally obtained.

[0079] Example 3 The only difference between this embodiment and Example 1 is the adjustment of the monomer dosage and reaction time for in-situ COF growth, controlling the COF layer thickness to 15 nm. Specifically, the dosage of TFPpy was adjusted to 7.4 mg, the dosage of Bcbpy to 5.8 mg, and the oil bath reaction time was extended to 48 h. All other raw materials, steps, and parameters remained consistent with Example 1. A lithium metal anode integrated material with a lithium metal layer thickness of 10 μm was finally obtained.

[0080] Example 4 The only difference between this embodiment and Embodiment 1 is that the vacuum evaporation time is adjusted to control the lithium metal layer thickness to 1 μm. All other raw materials, steps, and parameters remain the same as in Embodiment 1.

[0081] Example 5 The only difference between this embodiment and Embodiment 1 is that the vacuum evaporation time is adjusted to control the lithium metal layer thickness to 50 μm. All other raw materials, steps, and parameters remain the same as in Embodiment 1.

[0082] Example 6 The only difference between this embodiment and Embodiment 1 is that iron is used instead of cobalt in the single-atom metal. Specifically, CoCl2 is used instead of cobalt. 6H2O was replaced with an equimolar amount of FeCl2 Single-atom loading was performed using 2H2O, and the remaining raw materials, steps, and parameters were consistent with those in Example 1.

[0083] Example 7 The only difference between this embodiment and Example 1 is that a cyano-free COF monomer is used to construct the framework. Specifically, Bcbpy is replaced with an equimolar amount of 2,2'-bipyridine-5,5'-diamine (without cyano substitution) to obtain a cyano-free COF layer. All other raw materials, steps, and parameters are the same as in Example 1.

[0084] Example 8 The only difference between this embodiment and Example 1 is that the LLZO powder is not pretreated with Piranha solution hydroxylation and is directly used for in-situ COF growth. Specifically, the Piranha oxidation treatment step of LLZO is omitted, and the original LLZO powder is used directly for the COF growth reaction. All other raw materials, steps, and parameters are consistent with those in Example 1.

[0085] Example 9 The only difference between this embodiment and Example 1 is that the single-atom metal loading is impregnated with room temperature magnetic stirring instead of ultrasonic impregnation. Specifically, COF@LLZO and the metal salt are dispersed in methanol and stirred at room temperature for 12 hours instead of ultrasonic treatment for 4 hours. All other raw materials, steps and parameters are the same as in Example 1.

[0086] Comparative Example 1 This comparative example does not use any composite interface layer; lithium metal is directly vacuum-deposited onto the surface of an LLZO ceramic sheet. Specifically, a blank LLZO ceramic sheet is taken, and without COF growth, single-atom loading, or coating treatment, a 10 μm thick lithium metal layer is deposited directly according to the deposition parameters of Example 1 to obtain the control sample.

[0087] Comparative Example 2 This comparative example only grows a COF layer in situ on the LLZO surface, without loading any single-atom metal. Specifically, the LLZO pretreatment, COF in situ growth and coating were completed according to the steps of Example 1 to obtain a modified solid electrolyte containing only a COF layer; subsequently, a 10 μm thick lithium metal layer was deposited using the same parameters.

[0088] Comparative Example 3 In this comparative example, cobalt nanoparticles are loaded onto the COF layer to replace cobalt single atoms. Specifically, the CoCl2 in Example 1 is replaced with... The amount of 6H2O was increased to 50mg, and after impregnation, COF@LLZO loaded with Co nanoparticles was prepared by reduction at 300℃ in H2 atmosphere for 2h. The subsequent coating and evaporation steps were the same as in Example 1.

[0089] Comparative Example 4 This comparative example uses commercial lithium foil roll bonding instead of vacuum-deposited lithium metal layers. Specifically, the modified solid electrolyte prepared in Example 1 is used, and a 10 μm thick commercial lithium foil is bonded to its surface using a roll bonding process with a roll bonding pressure of 10 MPa.

[0090] Comparative Example 5 This comparative example directly loads cobalt components onto the LLZO surface without constructing a COF framework support. Specifically, blank LLZO powder is directly mixed with CoCl2. The 6H2O mixture is impregnated to allow cobalt ions to be directly adsorbed onto the LLZO surface. The subsequent coating and vapor deposition steps are the same as in Example 1.

[0091] Performance characterization methods and testing equipment All samples prepared in the examples and comparative examples were assembled and tested in an anhydrous and oxygen-free glove box under argon protection (H2O < 0.1 ppm, O2 < 0.1 ppm); the specific testing methods are as follows: (1) Interface impedance test: The interface impedance of the symmetrical cell was tested by electrochemical workstation using alternating current impedance spectroscopy (EIS). The test frequency range was 10 Hz. -2 ~10 6 Hz, AC amplitude 5 mV, test temperature 25℃.

[0092] (2) Critical current density test: The Blue Electric test system was used to perform stepped constant current charge and discharge on the symmetrical battery. The initial current density was 0.1 mA / cm². 2 Each stage of charging and discharging lasts for 0.5 hours, with the rate increasing by 0.1 mA / cm² at each stage. 2 Until a sudden drop in battery voltage causes a short circuit, the highest current density before the short circuit is recorded as the critical current density, in mA / cm². 2 .

[0093] (3) Cyclic stability test: The Blue Electricity test system was used at 0.5 mA / cm 2 Current density, 1 mAh / cm 2 The cycle life is defined as the duration of constant current charge-discharge cycles performed under the given capacity conditions, with the cycle time at which the battery experiences a significant short circuit or polarization voltage exceeding 200 mV being taken as the cycle life, measured in hours.

[0094] (4) Interfacial bonding strength test: The bonding strength between the composite interface layer and the solid electrolyte substrate was tested using the Anton Paar Revetest micro-scratch tester. The loading load range was 0~100 mN, the scratch length was 3 mm, and the loading rate was 100 mN / min. The critical load at which the interface layer showed obvious peeling and detachment was taken as the interfacial bonding strength, in mN.

[0095] The performance test results are shown in Table 1.

[0096] Table 1

[0097] As shown in Table 1, the interfacial impedance, critical current density, cycle life and interfacial bonding force of Examples 1-9 are all superior to those of Comparative Examples 1-5, proving the effectiveness of the integrated process of "COF porous confinement, single-atom metal chemical regulation and simultaneous construction by vapor deposition" of the present invention.

[0098] (1) The interfacial impedance of Example 1 is only 32 Ω·cm 2 Compared to Comparative Example 1, which directly deposits lithium without any interface layer, the current density is reduced by approximately 85%, and the critical current density is reduced from 0.2 mA / cm². 2 Increased to 1.2 mA / cm 2 The cycle life was extended from 50 h to 1000 h. Although the performance of Comparative Examples 2 and 5 was improved compared to Comparative Example 1, it was still significantly worse than that of Example 1, indicating that both the uniform nucleation sites provided by the COF porous framework and the regulation of interfacial electron distribution by the single-atom metal are indispensable. In Comparative Example 3, cobalt nanoparticles were used to replace cobalt single atoms, and the interfacial impedance increased to 89 Ω·cm. 2The cycle life dropped to 220 h, indicating that the cobalt in nanoparticle form has low dispersion and few effective active sites, making it impossible to uniformly control the local electric field like MN-coordinated and anchored single atoms. Comparative Example 4 used commercial lithium foil roll bonding. Although it used the same modified solid electrolyte as Example 1, its interfacial impedance was the highest among all samples. This is because the rigid lithium foil and the interface layer only form solid-solid point contact, which cannot achieve in-situ conformal bonding, resulting in a large number of interfacial voids. In contrast, during the vapor deposition process, gaseous lithium atoms nucleate and grow in-situ within the COF channels, forming a conformal and tight coupling with the interface layer. This proves that "simultaneous integration of lithium deposition and interface construction" is the key to obtaining a low-impedance interface.

[0099] (2) Effect of lithium metal layer thickness: The interfacial impedance and interfacial bonding force of the three are similar, indicating that the interfacial performance is mainly determined by the composite interfacial layer and is basically unrelated to the lithium layer thickness; the cycle life increases with the increase of lithium layer thickness, reaching 1200h in Example 5. When the lithium layer is too thin, the lithium storage is limited, and the polarization is prone to increase after lithium loss during long cycles, resulting in a relatively short life, but it is still significantly better than all comparative examples.

[0100] (3) In Example 6, after replacing cobalt with iron, the interfacial impedance increased to 49 Ω·cm. 2 The cycle life decreased to 510 h. This is because Co can form a Co-Li alloy with lithium in the early stage of lithium deposition, which can more effectively reduce the nucleation barrier. In addition, the Co-N coordination structure has a stronger ability to regulate the electronic distribution at the interface.

[0101] (4) Example 7 uses a cyano-free COF framework, and the critical current density is reduced to 0.7 mA / cm². 2 The cycle life decreased to 400 h, indicating that the cyano group, as a strong electron-withdrawing group, reduces the diffusion barrier of lithium atoms in the COF channels through Li-N coordination, and is an important structural factor for guiding the directional migration of lithium and realizing epitaxial dense growth.

[0102] (5) In Example 8, the Piranha pretreatment was omitted, and the interfacial bonding strength dropped sharply from 42 mN to 18 mN, while the interfacial impedance increased to 70 Ω·cm. 2 This is the worst among all embodiments. This is because without surface hydroxyl groups, the COF layer cannot form covalent bonds with the substrate through Schiff base condensation reaction, and only relies on physical adsorption. The interfacial bonding is weak and prone to voids, proving that in-situ chemical bonding growth is the basis for long-term interfacial stability.

[0103] (6) In Example 9, after replacing ultrasonic impregnation with room temperature magnetic stirring impregnation, the performance decreased significantly, indicating that the ultrasonic cavitation effect helps metal ions diffuse and penetrate into the COF channels and uniformly coordinate and anchor. Under conventional stirring, the cobalt dispersion is not uniform and some exist in an aggregated state, thus weakening the interface control effect.

[0104] In summary, this invention achieves uniform nucleation and dense growth of lithium on the surface of an electronically insulating solid electrolyte through the synergistic effects of a COF porous framework, single-atom metal, cyano-lithophilic sites, hydroxyl chemical anchoring, and vacuum evaporation. This results in an integrated lithium metal anode material with a continuous and dense lithium metal layer, tightly coupled to the solid electrolyte interface, exhibiting an interface impedance as low as 28 Ω·cm. 2 The critical current density reaches 1.2 mA / cm². 2 With a cycle life exceeding 1000 hours and an interfacial bonding force of 42 mN, it provides a practical and feasible technical solution for the construction of high-performance integrated solid-state lithium metal batteries.

[0105] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A lithium metal anode integrated material, characterized in that, It includes a modified solid electrolyte and a lithium metal layer physically deposited on the surface of the modified solid electrolyte, wherein the modified solid electrolyte includes a solid electrolyte substrate and a composite interface layer covering the surface of the solid electrolyte substrate; The composite interface layer includes a solid electrolyte, a covalent organic framework layer (COF), and a single-atom metal modified in the COF.

2. The lithium metal anode integrated material according to claim 1, characterized in that, The single-atom metal in the composite interface layer is at least one of cobalt, iron, or nickel.

3. The lithium metal anode integrated material according to claim 1, characterized in that, The covalent organic framework layer (COF) in the composite interface layer contains cyano groups.

4. The lithium metal anode integrated material according to claim 1, characterized in that, The solid electrolyte in the composite interface layer includes oxide solid electrolytes and sulfide solid electrolytes with hydroxyl groups on their surface.

5. The lithium metal anode integrated material according to claim 4, characterized in that, The oxide solid electrolyte includes at least one of LLZO and LLTO; the sulfide solid electrolyte includes at least one of LPSCl, LPSBr, LPSI and LGPS.

6. A method for preparing an integrated lithium metal anode material as described in any one of claims 1 to 5, characterized in that, Includes the following steps: S1, In-situ growth of a covalent organic framework layer (COF) on the surface of a solid electrolyte material; S2, Loading a single-atom metal onto the covalent organic framework layer COF to obtain a composite interface material; S3, the composite interface material is dispersed in a solvent to prepare a composite interface slurry; S4, the solid electrolyte substrate is coated with the composite interface slurry to obtain the modified solid electrolyte; S5, lithium metal is vapor-deposited on the modified solid electrolyte, so that gaseous lithium atoms grow along the composite interface layer on the surface of the modified solid electrolyte to form a lithium metal layer, thereby obtaining an integrated lithium metal anode material.

7. The preparation method according to claim 6, characterized in that, In S2, single-atom metals are loaded onto a covalent organic framework layer (COF) by ultrasonic impregnation.

8. The preparation method according to claim 6, characterized in that, The thickness of the covalent organic framework layer is 5~15 nm.

9. The preparation method according to claim 6, characterized in that, The thickness of the lithium metal layer is 1~50μm.

10. A solid-state lithium metal battery, characterized in that, The lithium metal anode integrated material as described in any one of claims 1 to 5, or the lithium metal anode integrated material prepared by the preparation method as described in any one of claims 6 to 9.